Inkjet technology for digital fabrication - Hutchings, Ian M.; Martin, Graham (Wiley, 2013)
Whilst inkjet technology is well-established on home and small office desktops and is now having increasing impact in commercial printing, it can also be used to deposit materials other than ink as individual droplets at a microscopic scale. This allows metals, ceramics, polymers and biological materials (including living cells) to be patterned on to substrates under precise digital control. This approach offers huge potential advantages for manufacturing, since inkjet methods can be used to generate structures and functions which cannot be attained in other ways. Beginning with an ov.
Includes index. - Includes bibliographical references and index. - Print version record and CIP data provided by publisher
Keywords: Microfluidics; Microfabrication; Ink-jet printing; Three-dimensional printing; Coating processes; Microfluidique; Impression par jet d'encre; Impression tridimensionnelle; Revêtement de surface; inkjet printing; 3-D printing; coating (process); TECHNOLOGY & ENGINEERING; Material Science